2014
DOI: 10.1111/1442-1984.12048
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen addition increases intraspecific competition in the invasive wetland plant Alternanthera philoxeroides, but not in its native congener Alternanthera sessilis

Abstract: Nitrogen is often released in pulses with different frequencies, and N supply pulses may affect growth, reproduction, and biomass allocation of plants. However, few studies have examined how N supply pulses affect intraspecific competition of clonal plants and whether such an effect depends on the N supply amount. We grew one (no competition) or 12 ramets (with intraspecific competition) of both an invasive clonal plant Alternanthera philoxeroides and its native congener Alternanthera sessilis in five differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…The quantity and frequency of N addition had a significant interactive effect on the total biomass and stem biomass of H. vulgaris. The results were consistent with a previous study [18]. Under low-quantity N addition, the total and stem biomass were significantly lower in the highcompared to the medium-and low-frequency N treatments.…”
Section: Effects Of N Addition Quantity and Frequency On The Growth Osupporting
confidence: 93%
See 1 more Smart Citation
“…The quantity and frequency of N addition had a significant interactive effect on the total biomass and stem biomass of H. vulgaris. The results were consistent with a previous study [18]. Under low-quantity N addition, the total and stem biomass were significantly lower in the highcompared to the medium-and low-frequency N treatments.…”
Section: Effects Of N Addition Quantity and Frequency On The Growth Osupporting
confidence: 93%
“…We predict that the effect of N deposition frequency on plants may be mediated by the quantity of N deposition. For example, under the conditions of low N deposition, the biomass of Alternanthera sessilis was higher in high-, compared to low-frequency N deposition, respectively [18]. Furthermore, the influence on different plant species varies with N deposition frequency.…”
Section: Introductionmentioning
confidence: 96%
“…With the water depth fluctuation, there are other sources of stress that could affect the growth of target plants, such as nitrogen pulses, changed water content and low nutrients (Sun, Ding, & Ren, 2009;Wang et al, 2015). Zhang et al (2016) suggested that increasing concentration of nutrients promoted growth of invasive Alternanthera philoxeroides and alleviated the stress of submergence.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on the biomass allocation pattern at different clonal growth stages are inconsistent with those of Goldberg and Novoplansky (1997), which measured the competitive effects on survival, but not on growth parameters and at different nutrient levels. The different results may be explained by differences in stress intensity (Pugnaire andLuque 2001, Brooker et al 2008), and the role of nutrient availability on competition has been subjected to contrasting results (Körner 2003, He and Bertness 2014, Roiloa et al 2014, Wang et al 2015. Our main objective was to evaluate the effect of the competition on the focal species when interacting with different neighbours at different levels of a resource gradients (low/high).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, both nutrient levels and root treatments affected the R/S ratio of the focal plant when interacting with a conspecific, distant relative and close relative only at the no segregation treatment (NS). Some studies have suggested that higher nutrients will result in more severe competition due to more root-shoot competition (Morris 2003, Wang et al 2015 while other studies have shown less competition at high nutrient level (Wilson andTilman 1993, Goldberg andNovoplansky 1997). Intraspecific plant interaction is more complicated because if plant recognizes its conspecific neighbor, it will not compete for resources even if the resource requirement of conspecifics are more similar than heterospecific ones.…”
Section: Discussionmentioning
confidence: 99%